IMPLEMENTATION OF LEAN TOOLS (KAIZEN AND 5S) IN STAINLESS STEEL JAPANESE COMPANY THROUGH INNOVATION - Santi Setyaningsih; Rucita Cahyawati Putri (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Innovation can be made from small thing in our routine. Seiri (sort),Seiton (set in order), Seiso (shine), Seiketsu (standardize), and Shitsuke (sustain)is 5 Japanese words which is a systematic technique that is closely related toefficiency. Kaizen has been widely recognized in the world as continuousimprovement through small steps which impact economically for the company.These systems help management to manage the workplace, improve disciplinary,decrease waste and increase productivity. Mory Industries Inc. is one of theJapanese-owned stainless steel manufacturing company that upholds qualitycontrol which contribute significantly to the implementation of Kaizen and 5S.This study explores innovation of Kaizen implementation which refers to 5S thatapplied on the production floor and also the office in a concrete way. Directobservation will be carried out as the basis of the methodology of this study.Without any record detail activity of 5S that should be done by the workers, buteach worker has already implemented as a habit in their daily work. Every year,Mory Industries Inc. always improves some workplace through Kaizen techniquein order to increase efficiency.Keywords: 5S, efficiency, innovation, kaizen, quality.